Implementasi Information Schema Database Pada PostgreSQL untuk Pembuatan Tabel Informasi dengan Menggunakan Python Di PT XYZ - Dimas Aji Bayu Prasetyo (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Abstract The rapid development of technology is increasingly affects and facilitates human work. Each year, new technologies emerge by offering the more advanced complex and effective features than similar previous technologies which already exist. Aged technologies is getting no longer adept and began to lose support from their development companies. Nowadays, XYZ Company is migrating its applications, which is built by using Oracle form to Webix and Flask. Due to the large number of forms, the migration process also takes a long time and demand many human resources to be involved. Therefore, the developers need to map the form to see the information about the table which includes column names, constraints, data types, and relationships between each table. Responding to this, XYZ Company created a library that utilizes PostgreSQL database schema information as a table which provides the information. It is expected that the use of schema information to be used as an information table which is able to make it easier for the developers in application making process and fastening the form migration process.